Effect of Acupuncture and Motor Imagery Therapy on Unilateral Spatial Neglect in Stroke Patients - Da LEI; Renming XIE; Honggui CAO; Yanru LI; Fanglue CHEN (康复学报)
Objective:To explore effects of acupuncture and motor imagery on the comprehensive function of patients with unilateral spatial neglect (USN) after stroke.Methods:Stroke patients with hemiplegia were evaluated by neuropsychological tests and 40 right hemispheric stroke patients out of them were identified with USN. These patients with USN were randomly assigned to 3 groups: 13 patients as the control group received conventional rehabilitation therapy, 13 patients as the observation group received motor imagery while received conventional rehabilitation therapy, the remain patients as the experiment group received acupuncture combined with both of conventional and motor imagery. These three groups were evaluated by Catherine Bergego Scale (CBS), Fugl-Meyer motor assessment scale (FMA), and Modified Barthel index (MBI) before and after treatment.Results:The patients both in observation group and experiment group had significantly descended scores of CBS, while elevated FMA scale and MBI after treatment, all P<0.01. But no statistically significant difference was observed in the control group, all P>0.05. The effect means descended scores of CBS, the increased FMA scale and MBI were not equal in the three groups. The effect in the experiment group is significantly better than the scores in the other groups, P<0.01. The effect in the observation group is significantly better than the scores in the control groups, P<0.01.Conclusion:Acupuncture and motor imagery can greatly improve the motor function and ADL by improving the USN in the patients after stroke.